2022
DOI: 10.1002/adma.202202709
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Lattice Dynamics in Photoexcited 2D Perovskites

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Syntheses and crystal structures of the six layered perovskites of interest were reported by Billing et al 2,4,19 As reported in this previous work, changing the organic spacer from four to six carbons, as well as from linear to cyclic carbon chains, induces slight shifts in the equatorial lead-iodide bonds that, in turn, causes blue-or red-shifting of the absorption and emission energies (Figures 1 and S1). 6 These equatorial Pb− I−Pb bond angles lead to emission energies of approximately 520, 515, 524, 493, 515, and 516 nm, respectively (Figure 1f).…”
Section: ■ Results and Discussionsupporting
confidence: 60%
“…Syntheses and crystal structures of the six layered perovskites of interest were reported by Billing et al 2,4,19 As reported in this previous work, changing the organic spacer from four to six carbons, as well as from linear to cyclic carbon chains, induces slight shifts in the equatorial lead-iodide bonds that, in turn, causes blue-or red-shifting of the absorption and emission energies (Figures 1 and S1). 6 These equatorial Pb− I−Pb bond angles lead to emission energies of approximately 520, 515, 524, 493, 515, and 516 nm, respectively (Figure 1f).…”
Section: ■ Results and Discussionsupporting
confidence: 60%
“…(b) Demonstration of in-plane and out-of-plane Bragg peaks of interest. (a–b) Reproduced with permission from ref . Copyright 2022 Wiley-VCH.…”
Section: Optoelectronic Properties Of 3d and 2d Halide Perovskitesmentioning
confidence: 99%
“…Cuthriell et al studied the nonequilibrium lattice response of BA and PEA n = 1 halide perovskites and reveal a suppressing line width narrowing in both transient X-rays and photoluminescent spectra at ∼1 ns time scales, suggesting a transient ordering of distorted octahedra (Figure 18 a,b). 369 Interestingly, Zhang et al has reported lattice dynamics beyond the Mott density and revealed an ultrafast relaxation of the lattice distortion at very short time, via reduced in-lane octahedral tilting (relaxation of antiferro-distortions) in DJ-type 2D halide perovskites (Figure 18 c−e). 370 Such strong carrier−lattice interactions are initiated by dense electron−hole plasma beyond the Mott density.…”
Section: Bulk Ferroelectricity In 2d Halide Perovskitesmentioning
confidence: 99%
“…Finally, deformation potential coupling to Pb–X–Pb bends should be present for other LHP systems with differing compositions (other A-cations or X-anions) or dimensions (for example, two-dimensional (2D) LHPs), provided the VB, CB or both consist of sp -bonding of the Pb–X sublattice. For example, photoinduced straightening of Pb–I–Pb bends has recently been reported in 2D LHPs 49 , 50 . The strength of the coupling and interactions, and therefore their relevance, depends on the particular LHP system.…”
Section: Mainmentioning
confidence: 99%